Kajian Model Interaksi pada Adsorpsi Logam Berat Kadmium (Cd2+) dengan Menggunakan Adsorben dari Pasir Hitam - Haryanto, Bode; K Sinaga, Warren; T Saragih , Febri (Jurnal Teknik Kimia USU, 2019)
This study aimed to analyze the adsorption ability of black sand in the metal ions adsorb cadmium (Cd2+) with a concentration of 70 ppm to a solution with a pH of 4,5. The black sand is used is 40 mesh. This research was conducted by batch adsorption system naturally and adsorption kinetics modeling. Kinetics of adsorption reached equilibrium at time t = 120 minutes with the percentage concentration of adsorbed Cd2+ 18,5%. In the adsorption kinetics modeling correlation coefficient is almost the same between the equations of first order and second order in the amount of 0.98 and 0.99. The result indicated that the type of interaction Cd2+ ions on the surface of black sands occur in chemistry and physics. The adsorption kinetics of diffusion modeling of internal and external diffusion of the correlation coefficient of 0,85 and 0,71. From this data it can be seen that in this study is modeling kinetic internal diffusion trend that shows adsorbent particles are inter sand surface area that experienced internal inter-particle pore diffusion.